Natural evolution of alkaline characteristics in bauxite residue. (1st February 2017) - Kong, Xiangfeng; Guo, Ying; Xue, Shengguo; Hartley, William; Wu, Chuan; Ye, Yuzhen; Cheng, Qingyu
Abstract: Bauxite residue, a highly alkaline solid waste, is extremely hazardous to the surrounding environment and current research approaches have largely focused on the removal and separation of alkaline substances. Natural weathering processes may be a step forward in terms of their regeneration. In this study, natural evolution of basic alkalinity, electrical conductivity, exchangeable ions and acid neutralizing capacity of residue in the disposal areas was discussed. Minerals, exchangeable cations and alkaline anions were analyzed by X-ray powder diffraction (XRD), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and titration, respectively. Acid neutralizing capacity was carried out by batch neutralization experiments. Basic alkalinity, electrical conductivity, cation exchange capacity and exchangeable sodium percentage decreased with increasing disposal duration. Sodium was the predominant exchangeable cation in fresh residue but its concentration significantly decreased with increasing time from initial disposal. The acid neutralizing capacity of bauxite residue was investigated by incubation with hydrochloric acid. Acid neutralizing capacity curves changed with disposal duration and each revealed a characteristic buffering behavior that could be controlled by its alkaline components. Graphical abstract: Highlights: ● Bauxite residue alkalinity is reduced following disposal. ● Bauxite residue reveals natural buffering behavior following disposal. ● Physicochemical conditions of disposed residues are being ameliorated over time. ● Natural remediation of BRDAs benefit surface revegetation and soil formation.